Computer Science &Amp; Information Technology 2018
DOI: 10.5121/csit.2018.80510
|View full text |Cite
|
Sign up to set email alerts
|

Reap-SoS: A Requirement Engineering Approach for System of Systems

Abstract: A System of Systems (SoS) is a class of system composed of a set or arrangement of independent systems that together provide unique functionality for the end user. Due to its complexity, the Requirement Engineering (RE) process needs to undergo adaptations to fit the development of this type of system. In this context, the objective of this work is to propose a approach for the development of SoS, called REAP-SoS. The main characteristic of the REAP-SoS is the derivation of the individual missions and requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The research community has realized that, due to the complexity of SoS, its requirements and processes need to undergo adaptations to fit the development and management of this type of architecture according to new trends. There are proposals for this field [6][7][8], addressing the modeling and design requirements; however, after careful study of the literature, it can be concluded that both research answers and practical guidance for comprehensive SoS management are incomplete and not mature enough yet.…”
Section: Introductionmentioning
confidence: 99%
“…The research community has realized that, due to the complexity of SoS, its requirements and processes need to undergo adaptations to fit the development and management of this type of architecture according to new trends. There are proposals for this field [6][7][8], addressing the modeling and design requirements; however, after careful study of the literature, it can be concluded that both research answers and practical guidance for comprehensive SoS management are incomplete and not mature enough yet.…”
Section: Introductionmentioning
confidence: 99%